Perspektif Iman Kristen Terhadap Ritual Mangalap Tondi Budaya Batak - Siregar, Benget Parningotan (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
The Mangalap Tondi ritual is a traditional practice in Batak Toba culture that aims to recall a person’s soul (tondi) believed to be lost or weakened. This study seeks to analyze the ritual from a Christian faith perspective, employing a qualitative approach through theological, anthropological, and cultural literature review. As the majority of Batak people are now Christians, a tension has emerged between ancestral beliefs and Christian teachings. The findings reveal a complex dynamic between the Mangalap Tondi tradition and Christian faith, particularly concerning the concepts of spirit, the power of God, and salvation. This study highlights the importance of a contextual approach in engaging with local cultural practices without compromising the integrity of Christian faith. The findings are expected to contribute to the development of contextual theology within modern Batak society.